Constitutional pluralism in the EU - Jaklic, Klemen, 1975- (Oxford : Oxford University Press, 2014)
This title offers an overarching examination of constitutional pluralism in the European context. Mapping the leading work to date, it offers a critical assessment of the problems and potential of pluralist theory, arguing that a refined version of constitutional pluralism should be considered the best account of European constitutionalism.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 14, 2014).
Keywords: Constitutional law -- European Union countries; Legal polycentricity -- European Union countries